2022
DOI: 10.2147/idr.s388166
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum and Lichtheimia corymbifera Co-Infection Due to Inhalation of Biogas in Immunocompetent Patients: A Case Series

Abstract: This is the first report describing co-infection of Scedosporium apiospermum and Lichtheimia corymbifera caused by biogas inhalation in two people without underlying medical conditions. Two patients fell into the same pig manure pit at the same time while rescuing another patient (this person died in a few hours) and inhaled biogas. Both patients were diagnosed with pulmonary fungal disease and developed acute liver failure around Day 52. Their results were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Importantly, the mAb does not crossreact with unrelated yeasts and moulds of clinical importance including Aspergillus spp., Candida and Cryptococcus spp., Mucorales spp., and species of Fusarium. This high degree of specificity is of critical importance given the occurrence of mixed fungal co-infections in humans [1,19,40,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the mAb does not crossreact with unrelated yeasts and moulds of clinical importance including Aspergillus spp., Candida and Cryptococcus spp., Mucorales spp., and species of Fusarium. This high degree of specificity is of critical importance given the occurrence of mixed fungal co-infections in humans [1,19,40,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…The dose of NAB for the treatment of pulmonary mucormycosis remains unclear 14 . Most data are from case reports where both lipid and non‐lipid formulations of amphotericin B have been used in varying doses 11,12,26 . In studies evaluating NAB for prophylaxis against IPA, LAMB has been shown to have a longer lung retention time than ABDC 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…lipid and non-lipid formulations of amphotericin B have been used in varying doses. 11,12,26 In studies evaluating NAB for prophylaxis against IPA, LAMB has been shown to have a longer lung retention time than ABDC. 8,9 The drug deposition in the lungs was similar with both formulations, but the clearing of Aspergillus fumigatus was better with LAMB.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…(Arndt et al, 2009;Bergantim et al, 2013;Henn et al, 2014;Obradovic-Tomasev et al, 2014;Pandey et al, 2019;Anita et al, 2021; Bellanger Benhadid-Brahmi et al, 2022;Johnson et al, 2021;Moorthy et al, 2021;Paul et al (2022); Ramıŕez-Hinojosa et al, 2021;Singh et al, 2021;Zayet et al, 2021;Rahna et al, 2022;Suresh et al, 2022;Tabarsi et al, 2022;Teng et al, 2022;Zhan et al, 2022;Murray et al, 2023;Sardeshmukh et al, 2023), Fusarium spp. (De Almeida Junior et al, 2015;Marino et al, 2023), Candida albicans (Obradovic-Tomasev et al, 2014;Pandey et al, 2019;Jawanda et al, 2022), Cryptococcus neoformans (Henn et al, 2014;Gupta et al, 2023), Lomentospora prolificans (Erami et al, 2023), and Scedosporium apiospermum (Shand et al, 2004;Marques et al, 2011;Song et al, 2022;Kanaujia et al, 2023).…”
Section: Discussionunclassified